Sexism in the advertising discourse of Ukraine: Analysis of «Jinsovik» and «El Paso» advertising - Nadiya Viytalyuk; Yuliia Maslova (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The article highlights the reasons for the use of sexist advertising by Ukrainian companies and the impact of such phenomena on a woman's social image and general well-being, as well as consumer culture. Although there is a more entrenched view of equality in the Western world today, sexism still prevails in advertising. It is believed that the way women are portrayed in advertising affects how a woman's role in society is perceived and how a woman should act and behave. The specific purpose of this study was to analyze promotional videos of the company Jinsovik and the El Paso Tavern in 2020 to demonstrate the use of sexualization and objectification of women. Apart from research implications, the findings also emphasize the feasibility of making specific control decisions related to the work of the executive bodies of the Office of Advertising, information and advertising departments and utilities.